Flexible Education - A Paradigm Shift in Engineering Pedagogy - Ardalan, Alireza A.; Molaeian, Shaghayegh (Journal of Engineering Education Transformations, 2025)
This research presents a novel pedagogical model termed “Flexible Education”, designed to tailor learning experiences to the unique needs of each student and align educational content with the dynamic job market. Unlike traditional methods, “Flexible Education” fosters an inclusive learning environment through e-learning, ongoing assessment, and active student participation. At the heart of our methodology are several fundamental principles: flexible teaching strategies, real-time elearning resources, problem-based learning, active learning techniques, and feedback mechanisms. We employ assessment methods such as student-led presentations and group activities to stimulate critical thinking and digital literacy. Workshops and collaborative sessions are integral to our model, aiming to equip students with essential skills for their future professions. Our empirical analysis, based on student performance indicators, demonstrates significant improvements in critical thinking, engagement, technological proficiency, teamwork, and problem-solving abilities. This underscores the effectiveness of the “Flexible Education” model in enhancing various aspects of student learning.